Incongruence between confirmed and suspected clinical cases of Japanese encephalitis virus infection - Li, Wei; Feng, Yuliang; Zhong, Hongrong; Jiang, Mingfeng; Zhang, Jiake; Lin, Shihua; Chen, Na; He, Shusen; Zhang, Kai; Fu, Shihong; Wang, Huanyu; Liang, Guodong (Frontiers in Cellular and Infection Microbiology, 2024)
Background Japanese encephalitis (JE) is a notifiable infectious disease in China. Information on every case of JE is reported to the superior health administration department. However, reported cases include both laboratory-confirmed and clinically diagnosed cases. This study aimed to differentiate between clinical and laboratory-confirmed cases of Japanese encephalitis virus (JEV) infection, and improve the accuracy of reported JE cases by analyzing the acute-phase serum and cerebrospinal fluid of all reported JE cases in the Sichuan province from 2012 to 2022. Methods All acute-phase serum and/or cerebrospinal fluid samples of the reported JE cases were screened for IgM(ImmunoglobulinM)to JEV using the enzyme-linked immunosorbent assay (ELISA), and the detection of the viral genes of JEV and 9 other pathogens including enterovirus (EV), using reverse transcription PCR was attempted. Epidemiological analyses of JE and non-JE cases based on sex, age, onset time, and geographical distribution were also performed. Results From 2012 to 2022, 1558 JE cases were reported in the Sichuan province. The results of serological (JEV-specific IgM) and genetic testing for JEV showed that 81% (1262/1558) of the reported cases were confirmed as JEV infection cases (laboratory-confirmed cases). Among the 296 cases of non-JEV infection, 6 viruses were detected in the cerebrospinal fluid in 62 cases, including EV and the Epstein-Barr virus (EBV), constituting 21% (62/296) of all non-JE cases. Among the 62 non-JEV infection cases with confirmed pathogens, infections with EV and EBV included 17 cases each, herpes simplex virus (HSV-1/2) included 14 cases, varicella- zoster virus included 6 cases, mumps virus included 2 cases, and human herpes viruses-6 included 1 case. Additionally, there were five cases involving mixed infections (two cases of EV/EBV, one case of HSV-1/HSV-2, one case of EBV/HSV-1, and one case of EV/herpes viruses-6). The remaining 234 cases were classified as unknown viral encephalitis cases. Our analysis indicated that those aged 0–15 y were the majority of the patients among the 1558 reported JE cases. However, the incidence of laboratory-confirmed JE cases in the >40 y age group has increased in recent years. The temporal distribution of laboratory-confirmed cases of JE revealed that the majority of cases occurred from May to September each year, with the highest incidence in August. Conclusion The results of this study indicate that there is a certain discrepancy between clinically diagnosed and laboratory-confirmed cases of JE. Each reported case should be based on laboratory detection results, which is of great importance in improving the accuracy of case diagnosis and reducing misreporting. Our results are not only important for addressing JE endemic to the Sichuan province, but also provide a valuable reference for the laboratory detection of various notifiable infectious diseases in China and other regions outside China.